The Role of School Committee in Supporting The Fulfillment of Education Facilities and Infrastructure - Herwan Herwan; Aswandi Aswandi; M. Chiar (JETL (Journal of Education, Teaching and Learning), 2018)
This study aims to determine the role of school committees in supporting the fulfillment of educational infrastructure facilities at State Vocational High School 1 Teluk Keramat (SMKN 1 Teluk Keramat) by identifying and describing the role and involvement and form of support provided and the factors that influence it. This research uses qualitative descriptive approach. the results of the research that has been done are 1) School Committee SMKN 1 Teluk Keramat has performed its role as an advisory agency, as a supporter agency, as a controlling agency, and as mediator agency; 2) Supporting factors for the school committee include a) Good collaboration of schools; b) Authority granted by the school to the school committee in carrying out its duties; c) Compulsory responsibility of completing the compulsory education of 12 years of learners; d) To carry out the mandate of the Law on National Education System Number 20 of 2003 and Permendikbud Number 75 concerning School Committees; 3) Inhibiting factors for school committees are a) Lack of coordination between schools and school committees; b) Be more concerned with personal matters than school committee duties; c) lack of awards earned as school committees; d) Ineffective committee managers due to the distance from schools; 4) Not all school committee members are actively involved.